Crystallization mechanism control during epitaxy from solution-melt - Baganov, Ye.O.; Shutov, S.V. (Functional Materials, 2006)
Main problems appearing during heteroepitaxy from solution-melts and requirements to time-temperature profiles at the crystallization front have been considered. The substrate cooling possibility by gas feeding to the reactor from outside to provide the crystallization conditions that consecutively combine properties both pulse and quasi-equilibrium conditions growth methods dare shown. A model of heat and mass transfer for a priori determination of the cooling gas consumption has been examined experimentally.